An innovative method to quantitate tissue integration of hyaluronic acid‐based dermal fillers - Dugaret, A. S.; Bertino, B.; Gauthier, B.; Gamboa, B.; Motte, M.; Rival, Y.; Piwnica, D.; Osman‐Ponchet, H.; Bourdès, V.; Voegel, J. J. (Skin research and technology, 2018)
Background/purpose Following intradermal injection, hyaluronic acid (HA)‐based fillers tend to spread within the reticular dermis and to distribute between the dermal fibers. This biointegration is commonly measured qualitatively using histological methods. We developed a “toolbox” consisting of a visual scoring and a semi‐automatic image analysis method using internal developed algorithm to quantitate the biointegration of Restylane® in histological sections. Methods Restylane® was injected intradermally in the abdominal skin of 10 healthy human subjects scheduled for abdominoplasty. The injections were performed either in vivo before surgery or ex vivo on samples taken post‐surgery at different time points. The samples were processed for histology by visual scoring and image analysis using algorithms developed in Definiens to assess biointegration. Results The image analysis segmentation was accurate with <5% manual changes. Furthermore, the results calculated with the semi‐automatic method were consistent with the visual scores obtained on injected human skin samples by means of a 5‐grade photographic scale. A modified hematoxylin‐eosin staining was found adequate to visualize both, the filler and the general morphology, on the same section. An excellent correlation was observed between the integration results obtained with PAS/Alcian Blue and HE‐stained slides, allowing for a single staining in future studies. Conclusion We developed a modified HE staining histological method and a new histomorphometric image analysis tool to quantitate biointegration of HA‐based fillers in human skin. The results obtained in this study confirmed the known intermediate biointegration properties of Restylane®, thus validating these innovative methods.